The Portrayal of The Main Characterâ€™s Struggle Against Capitalist Society In â€œThe Shawshank Redemptionâ€ Movie By Frank Darabont - Stephen Ali Barkah; Rasiah Rasiah; Nur Israfyan Sofian (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
This research is concerned to reveal the portrayal of the main characterâ€™s struggle against capitalism in the Shawshank Redemption movie. According to the purpose of this research, the researcher uses marxism as the basic theory related to the class struggle. The research question of this research is â€œHow is the portrayal of the main characterâ€™s struggle against capitalism in Shawshank Redemption movie?â€. The data in the research is collected through watching the movie intensively, identifying the data in detail which referred to the Marxism class struggle perspective, and cataloging the data by sorting the data analyzed in Marxism theory. The technique of data analysis is done through analyzing the data descriptively and interpretatively in showing the portrayal of the main character's struggle in getting his freedom and defeating capitalism in The Shawshank Redemption movie. The researcher uses qualitative descriptive analysis as the method to analyze how capitalism works in the prison institution in the movie. The research found that there is a distinction between the two social classes in the prison, the bourgeoisie, and the proletariat. The research found that Andy as the main character treated differently before and after being a prisoner, so he did the struggle by using his intellectuality to defeat the capitalists in the prison. In the conclusion, the researcher found the relationship with the position of the Capitalist triggers them to oppress the prisoners in the Shawshank prison, and the process of the main characterâ€™s in defeating the capitalist society.